Jointgraph: A DAG‐based efficient consensus algorithm for consortium blockchains. (5th September 2019) - Xiang, Fu; Huaimin, Wang; Peichang, Shi; Xue, Ouyang; Xunhui, Zhang
Summary: The blockchain is a distributed ledger that records all transactions and operations in a shared manner. Public blockchains such as Bitcoin realize decentralization at the cost of mining overhead, which is not suitable for real‐life scenarios requiring high throughput. Techniques such as the consortium blockchain improve efficiency through partial decentralization. However, the consensus algorithms used in the existing state‐of‐the‐art consortium blockchains face many challenges when dealing with commercial applications. For example, the high communication overhead hinders the scalability of PBFT‐based consensus algorithms even though they are efficient at small scale. Hashgraph, one of the most popular Directed Acyclic Graph‐based (DAG‐based) consensus algorithms, achieves good performance in scalability; however, it does not allow users' dynamic participation. To deal with these challenges, we propose Jointgraph, a Byzantine fault‐tolerance consensus algorithm for consortium blockchains based on DAG. In Jointgraph, transactions are packed into events and validated by no less than 2/3 of all members. A supervisor is introduced in our design, who monitors member behaviors and improves consensus efficiency. Simulation results demonstrate that Jointgraph outperforms Hashgraph in both throughput and latency.